SIGMA: Wireless System with Geolocation for Environmental Monitoring - Christian Tipantuña; Jeaneth Acero; Christian Reyes; Danny S. Guamán; José Estrada-Jiménez (Latin-American Journal of Computing)
The increase in the number of automotive parks, the emissions generated by industries, and the forest fires, among others, deteriorate the air quality of the Metropolitan District of Quito. Low-cost devices (sensors) distributed throughout the city to collect and deliver information on concentrations of gaseous pollutants in real time are essential for preserving the health of the citizens. This kind of technology can contribute to improving air quality by controlling the emissions of harmful substances into the atmosphere. This paper shows a prototype system for environmental monitoring using open hardware and software technologies. The system comprises two subsystems: a transmitter (mobile) and a receiver (fixed). The transmitter unit has been installed in a public transport vehicle (a taxi or any public transportation), which allows the acquisition of environmental parameters such as carbon monoxide, ozone, nitrogen, temperature, humidity, geographic location, time, and date. The obtained measurements are sent in real-time to a receiver subsystem, mainly consisting of a server, where the received data is processed and published in a pollution map. This data informs citizens by geographical areas, about the different levels or concentration ranges of a particular gas, and general air pollution in the city.